2006
DOI: 10.1111/j.1365-2699.2006.01642.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of genetic differentiation in Thamnophis and Taricha from the Pacific Northwest

Abstract: Aim  The co‐evolutionary interaction between the common garter snake, Thamnophis sirtalis, and the rough‐skinned newt, Taricha granulosa, takes place throughout much of the Pacific Northwest (North America). The biogeography of the Pacific Northwest has been heavily influenced by the last Pleistocene glaciation, which reached a maximum as late as 14,000 yr bp. We researched: (1) what type of population structure is present for garter snakes and newts, (2) whether the population structure of these species is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 97 publications
(145 reference statements)
3
11
0
Order By: Relevance
“…Further, an sPCA found no significant geographic structure suggesting that, in reality, garter snakes across our study area represent a single genetic population. This result is supported by previous studies that found low levels of genetic differentiation among subpopulations of T. sirtalis separated by large distances, in surveys using both microsatellites (Ridenhour et al, 2007) and allozymes (King & Lawson, 2001).…”
Section: Genetic Population Structuresupporting
confidence: 88%
See 1 more Smart Citation
“…Further, an sPCA found no significant geographic structure suggesting that, in reality, garter snakes across our study area represent a single genetic population. This result is supported by previous studies that found low levels of genetic differentiation among subpopulations of T. sirtalis separated by large distances, in surveys using both microsatellites (Ridenhour et al, 2007) and allozymes (King & Lawson, 2001).…”
Section: Genetic Population Structuresupporting
confidence: 88%
“…However, no individual for any garter snake locus failed to amplify implying that null alleles are not a pervasive problem. Previous tests by the researchers that developed or used the microsatellites used here reported no significant departures from HWE with the exception of TS1 and TS2 (McCracken et al, 1999;Prosser et al, 1999;Garner et al, 2004;Ridenhour et al, 2007). Bittner & King (2003) investigated the population structure of garter snakes from Lake Erie and southwestern Ontario using both allozymes and DNA microsatellites, including loci TS1 and TS2.…”
Section: Genetic Population Structurementioning
confidence: 94%
“…() and Ridenhour et al. () also reported low estimates of population subdivision among sites in Oregon and Washington, suggesting that Ta. granulosa may exhibit low site fidelity.…”
Section: Discussionmentioning
confidence: 96%
“…However, we found support for range expansion for only 3 populations. Low genetic variation in the Pacific Northwest has been attributed to range expansion following glacial recession (Edmands 2001;Ridenhour et al 2007).…”
Section: August 2010mentioning
confidence: 99%